Knowledge and Pattern of Preventive Behaviors Among Relatives of Breast Cancer Patients in Yogyakarta Pre and During the COVID-19 Pandemic - Triratnawati, Atik; Mulyasari, Runavia (UI Scholars Hub, 2023)
Breast cancer is still one of the leading causes of death in Indonesia. The multifactorial causes of breast cancer, including heredity, carries a risk for the sufferers’ relatives. Vigilance in female relatives of breast cancer patients increases due to hereditary risk factors for having the same disease. This anthropological study aimed to reveal the mosaic of breast cancer patients’ female relatives’ knowledge of such a risk and their efforts to prevent it. Qualitative data collection through interviews was conducted with 13 female family members of breast cancer patients in Yogyakarta aged 17-65 years. The data analysis was done through an emic approach by examining the informants’ views on the situation and their solutions. All of the informants believed that breast cancer is a malignant and deadly disease if it is not detected early and not properly treated. They were all fully aware of their risk as a family member to have the same disease. Their preventive measures included medical (early examination, breast self-examination, laboratory check, or consultation with the doctor) and non-medical (changes in eating and drinking behavior, reducing stress, exercising, and wearing masks). Besides, they also made religious efforts by praying to God to be given a healthy life and for the patients to be healed and their offspring to be free from this disease.